1992
DOI: 10.1002/j.1460-2075.1992.tb05090.x
|View full text |Cite
|
Sign up to set email alerts
|

Truncated variants of gp120 bind CD4 with high affinity and suggest a minimum CD4 binding region.

Abstract: The envelope glycoprotein, gp120, of human immunodeficiency virus type 1 (HIV‐1) binds the cellular protein CD4 with high affinity. By deletion we show that 62 N‐ and 20 C‐terminal residues along with the V1, V2 and V3 variable regions of gp 120 are unnecessary for CD4 binding. A 287 residue variant (ENV59), missing those 197 amino acids, binds to CD4 with high affinity. A polyclonal antibody failed to efficiently precipitate ENV59 which is consistent with the loss of immunodominant antigenic structures in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 38 publications
12
64
0
Order By: Relevance
“…Whereas early studies indicated that this site was located in the fourth conserved (C4) domain of gp120 [58], mutational analysis and delineation of epitopes for anti-gp120 mAbs that block binding to CD4 have demonstrated that amino acid residues critical for CD4 binding are scattered throughout gp120 [59][60][61][62]. The current consensus view is that the CD4 binding site of gp120 is a complex folded structure in which amino acid residues from diverse regions are brought in close proximity [63].…”
Section: Hiv-1 Envelope Proteins and Phenotype Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas early studies indicated that this site was located in the fourth conserved (C4) domain of gp120 [58], mutational analysis and delineation of epitopes for anti-gp120 mAbs that block binding to CD4 have demonstrated that amino acid residues critical for CD4 binding are scattered throughout gp120 [59][60][61][62]. The current consensus view is that the CD4 binding site of gp120 is a complex folded structure in which amino acid residues from diverse regions are brought in close proximity [63].…”
Section: Hiv-1 Envelope Proteins and Phenotype Variabilitymentioning
confidence: 99%
“…As the gp120 binding site of CD4 consists primarily of positively charged amino acid residues it seems unlikely that these domains are directly involved in binding to V1 of CD4 [63,101]. Since recombinant gp120 proteins lacking V2 and V3 bind with similar affinity to CD4 as wild-type gp120 [62], V2 and V3 are more likely to be involved in postbinding and/or fusion events, i.e. by allowing increased exposure of the fusion domain of gp41 [72,102].…”
Section: Si Capacitymentioning
confidence: 99%
“…These conserved regions are thought to constitute the functional core of the glycoprotein and include a number of hydrophobic residues. This core structure has been shown to include the minimal CD4 receptor binding site, such that deletion of the first, second and third variable regions of the Env glycoprotein results in a truncated protein capable of binding CD4 with an affinity comparable to that of the parental molecule (lefts et al, 1996;Pollard et al, 1992;Wyatt et al, 1993). Given the level of variation present in env, and the probable plasticity of the molecule, it is important to define interactions between domains and their possible role in glycoprotein function.…”
Section: Envelope Determinants Of Tropism and Cytopathicitymentioning
confidence: 99%
“…However, for gp120 no single domain responsible for receptor binding has been identified, and the site of CD4 interaction is believed to involve discontinuous residues in the polypeptide sequence (Olshevsky et a]., 1990). Previous studies where truncated forms of gp 120rob from the HXB2 clone were expressed have identified regions of the gp120 linear sequence essential for maintenance of CD4 binding (Pollard et al, 1991(Pollard et al, , 1992Wyatt et al, 1993). Although there is no clear domain structure, the V1, V2 and V3 regions, and parts of both termini, could be removed without disrupting CD4 binding.…”
Section: Introductionmentioning
confidence: 99%
“…This further suggests that removal of variable regions may lead to enhanced exposure of conserved gp120 regions, which may normally be exposed only by conformational changes accompanying the fusion process (Matthews et al,I994). Thus, truncated forms of the gp120 molecule may be useful for vaccine development and may induce antibodies capable of recognizing epitopes conserved between divergent viral isolates (Pollard et al, 1992;Wyatt et al, 1993).…”
Section: Introductionmentioning
confidence: 99%